(Inadvertently) Instructing Missionaries in (Public University) World Religions Courses: Examining a Pedagogical Dilemma, its Dimensions, and a Course Section Solution. (January 2017) - Karapanagiotis, Nicole
Abstract: In this article, I explore an ethical and pedagogical dilemma that I encounter each semester in my world religions courses: namely, that a great number of students enroll in the courses as part of their missionary training programs, and come to class understanding successful learning to mean gathering enough information about the world's religious "traditions" so as to effectively seduce people out of them. How should we teach world religions – in public university religious studies courses – with this student constituency? What are/ought to be our student learning goals? What can and should we expect to accomplish? How can we maximize student learning, while also maintaining our disciplinary integrity? In response to these questions, I propose a world religions course module, the goal of which is for students to examine – as objects of inquiry – the lenses through which they understand religion(s). With a recognition of their own lenses, I argue, missionary students become more aware of the biases and presumptions about others that they bring to the table, and they learn to see the ways in which these presumptions inform what they see and know about others, and also what they do not so easily see.